Programming media art using processing : a beginner's guide - Noble, Margaret (Performance artist) (Boca Raton : Chapman & Hall/CRC, 2021)
Programming Media Art Using Processing: A Beginner's Guideprovides an entry-level exploration into visual design through computer programming using the open source and artist-friendly language, Processing. Used by hundreds of students, this learning system breaks lessons down into strategic steps towards fun and creative media art projects. This book provides a linear series of lessons with step-by-step examples that lead to beginning media art projects, including abstract designs, pixel landscapes, rollover animations, and simple video games. Computer programming can be overwhelming for the first-time learner, but this book makes the learning of code more digestible and fun through a full color, well-diagrammed, and deeply explained text presentation. Lessons are rhythmically broken down into digestible parts with code annotations and illustrations that help learners focus on the details one step at a time. The content is legible, flexible, and fun to work with because of its project-based nature. By following the lessons and producing the projects sequentially in this book, readers will develop the beginning foundational skills needed to understand computer programming basics across many languages and also explore the art of graphic design. Ultimately, this is a hands-on, practical guide. To learn more about Margaret Noble's work, please visit her artist's website and educator website.
Acknowledgements and Contributor List Author Bio Introduction and Best Practices Chapter 1: Designing Graphically with the Language of Code Getting Started & Basic Overview Lesson 1.1: Pixel Grid System Lesson 1.2: Code and Canvas Windows Lesson 1.3: More Shapes Lesson 1.4: Grayscale Lesson 1.5: Syntax, Comments, and Order of Code Lesson 1.6: Line Commands (Stroke and No Stroke) Lesson 1.7: Coloring Pixels Lesson 1.8: Adding Transparency Values Lesson 1.9: The Processing Reference -- Important Resource! Project: Geometric Design Chapter 2: Creating Responsive Environments Lesson 2.1: Dynamic Computer Programs Lesson 2.2: First Animations Lesson 2.3: Animation Trails Lesson 2.4: Finding Exact Coordinates Lesson 2.5: Complex Shapes Lesson 2.6: Linking Shapes for Synched Movement Lesson 2.7: Adding Text Lesson 2.8: Rotating Shapes Project: Interactive Environment Chapter 3: Automated Animations Lesson 3.1: Counting Variables Lesson 3.2: Moving Objects in Multiple Directions Lesson 3.3: Growing Shapes with the Mouse Lesson 3.4: Println() for Debugging Lesson 3.5: Constrain() for Stopping Animations Lesson 3.6: Random() Opportunities Lesson 3.7: Automated Rotations Project: Automated Environment Chapter 4: Animated Collages Lesson 4.1: Preparing and Importing Imagery Lesson 4.2: Moving Images Lesson 4.3: Fading and Coloring Images using Tint() Lesson 4.4: Resizing Images & Multiples Lesson 4.5: Constraining Mouse Movements Lesson 4.6: Void Key Pressed() and Image Rotations Lesson 4.7: Create Fonts Lesson 4.8: Project Optimization and noSmooth() Project: Animated and Interactive Collage Chapter 5: Conditional Interactions and Rollovers Lesson 5.1: Conditional Statements and Relational Operators Lesson 5.2: Conditional Statements with Custom Variables Lesson 5.3: And vs. Or Lesson 5.4: Logical Operators Defining Spaces Lesson 5.5: Variations with Mouse and Keyboard Actions Lesson 5.6: Two Variables: Alternating Movements Lesson 5.7: Color Detection Using the Get() Function Project: Rollover Animation Chapter 6: Events and Interactions for Simple Games: Part 1 Lesson 6.1: Turning Things on with Boolean Variables Lesson 6.2: Toggling Between Two States Using Boolean Variables Lesson 6.3: Multiple Buttons Alternating Lesson 6.4: Booleans Working with Counting Variables Lesson 6.5: Specific Keyboard Interactions Lesson 6.6: Creating a Walking Character Lesson 6.7: Boundaries Chapter 7: Events and Interactions for Simple Games: Part 2 Lesson 7.1: Timers Lesson 7.2: Continuous Motion Key Controls Lesson 7.3: For Loops are Efficient Lesson 7.4: Color Detection with For Loops Lesson 7.5: Game Creation from Keys, Loops, and Color Detection Lesson 7.6: Image Collisions with the Distance() Function Lesson 7.7: Two Players, Directional Movement, and Jumping! Chapter 8: Multilevel Architectures and Arrays Lesson 8.1: Basic Levels Architecture Lesson 8.2: States within Levels Lesson 8.3: Arrays Lesson 8.4: Image Arrays Lesson 8.5: Player Options Lesson 8.6: Choice Based Projects Conclusion Final Project: Multilevel Interactive Experience
OCLC-licensed vendor bibliographic record.
Keywords: Processing (Computer program language); Computer graphics -- Computer programs; New media art; COMPUTERS / Computer Graphics / General; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Interactive & Multimedia